Frontiers of Combining Systems: 14th International Symposium, FroCoS 2023, Prague, Czech Republic, September 20–22, 2023, Proceedings - Sattler, Uli; Suda, Martin (Lecture Notes in Computer Science; Lecture Notes in Artificial Intelligence, 2023)
This book constitutes the refereed proceedings of the 14th International Symposium on Frontiers of Combining Systems, FroCoS 2023, held in Prague, Czech Republic, in September 2023. The symposium was co-located with the 32nd International Conference on Automated Reasoning with Analytic Tableaux and Related Methods, TABLEAUX 2023. The 14 papers presented were thorouhgly reviewed and selected from the 22 high-quality paper submissions. They are grouped in the volume according to the following topic classification: analysis of programs and equations; unification; decidable fragments; frameworks; higher-order theorem proving. This is an open access book.